2020
DOI: 10.1186/s12905-020-00985-9
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological hysterectomy in Northern Tanzania: a cross- sectional study on the outcomes and correlation between clinical and histological diagnoses

Abstract: Background: Hysterectomy is one of the most common gynaecological procedures performed worldwide. The magnitude of the complications related to hysterectomy and their risk factors are bound to differ based on locations, availability of resources and level of surgical training. Documented complications rates and their correlates are reported from high income countries while data from low-and middle-income countries including Tanzania is scare. Methods: This was a hospital based cross-sectional study conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…(10) The mean age of women who underwent hysterectomy due to gynecological disorders in our study was 47.8 years in accordance with several studies conducted in Pakistan and abroad where the mean ages found were 48.8 years 46.86 years, 45.76years, 45 years, 43 years and 40.37years respectively. (2,11,12,13,14,15) Most (78/190) 41.1% of these women were between ages 41 to 50 years, comparable to the studies conducted by Shahid R, Egbe TO and Imam ZS. (15,13,16) Irregular excessive bleeding and pain were the most frequent presenting complaints in our study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…(10) The mean age of women who underwent hysterectomy due to gynecological disorders in our study was 47.8 years in accordance with several studies conducted in Pakistan and abroad where the mean ages found were 48.8 years 46.86 years, 45.76years, 45 years, 43 years and 40.37years respectively. (2,11,12,13,14,15) Most (78/190) 41.1% of these women were between ages 41 to 50 years, comparable to the studies conducted by Shahid R, Egbe TO and Imam ZS. (15,13,16) Irregular excessive bleeding and pain were the most frequent presenting complaints in our study.…”
Section: Discussionsupporting
confidence: 80%
“…(9,16,19) However, leiomyomas and adenomyosis were the most frequent myometrial histopathological lesions and indication for hysterectomy in our study, in keeping with several other studies. (11,20,21) The most common type of hysterectomy was TAH without tubes and ovaries in our study. This is in accordance with several other studies where number of total abdominal hysterectomy was much more than vaginal hysterectomies.…”
Section: Discussionmentioning
confidence: 52%
“…About 600,000 hysterectomies are performed annually in the United States (4)(5)(6) . In Nigeria, 28% of all major gynecological operations performed are hysterectomies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Frequent use of the abdominal approach has been observed in many African countries, especially in parts of sub-Saharan Africa. [7][8][9][10] In these areas, surgery in this region. Little documentation exists in the literature to account for the role of minimally invasive surgery in the sub-Saharan Africa.…”
mentioning
confidence: 99%
“…In Africa, vaginal hysterectomy for benign conditions has never been well established and the abdominal approach still dominates, although this approach has been associated with high complication rates, as demonstrated in several reviews 3,4 . Frequent use of the abdominal approach has been observed in many African countries, especially in parts of sub‐Saharan Africa 7‐10 . In these areas, health‐related resources are limited, and one would expect the vaginal approach to be dominant as abdominal hysterectomy is associated with higher cost in relation to longer in‐hospital stay, higher rate of infection etc.…”
mentioning
confidence: 99%